Pemanfaatan Tanah Wakaf oleh Nadzir untuk Kepentingan Pribadi - Rahayu, Eka (CV. ULIL ALBAB CORP, 2025)
This research examines the concept of waqf from the perspective of muamalah fiqh and legislation in Indonesia, with a focus on the role of nadzir as waqf managers. Waqf is a form of charity that allows giving assets for the benefit of society. This research aims to explore the conditions that must be met to become a nadzir and their responsibilities in managing waqf assets in accordance with Law Number 41 of 2004 and Government Regulation Number 42 of 2006. The methods used are literature studies and interviews with nadzir in the field. The results show that the existence of nadzir is very important to maintain and develop waqf assets so that they are useful in a sustainable manner. Nadzir must have legal skills, creativity, and be trustworthy in management. This research also identifies the challenges faced by nadzir in carrying out their duties and the importance of public awareness regarding waqf administration. It is hoped that these findings can contribute to the development of more productive and sustainable waqf practices in Indonesia.